PERBAIKAN CITRA MALAM (TIDAK INFRARED) DENGAN METODE HISTOGRAM EQUALIZATION DAN CONTRAST STRETCHING - Sidik Sidik; Firmansyah Firmansyah; Syaiful Anwar (LPPM Nusa Mandiri, 2019)
Images taken with a digital camera with ambient lighting that is lacking will produce a dark image and it is difficult to recognize objects inside. In such conditions, image enhancement (image enhancement) is needed in order to get an image display with a better form of visualization. Many techniques or methods are used in image enhancement. This research has produced an application program to improve the quality of night images with the histogram smoothing method (Histogram Equalization) and contrast stretching (Contrast Stretching) as well as the smoothing method and the median filter method to eliminate noise. The parameters measured in improving the image quality of the night based on the methods used are the peak signal-to-noise ratio (PSNR). The results of this study are that night image quality (not infrared) can be improved by several methods, namely: grayscale, smoothing, histogram equalization and contrast stretching as preprocessing and multiply as the final process. The level of accuracy of improving the quality of night images (not infrared) is 85%.